Multifunctional Lignin-Based Composite Materials for Emerging Applications - Ma, Chang; Kim, Tae-Hee; Liu, Kun; Ma, Ming-Guo; Choi, Sun-Eun; Si, Chuanling (Frontiers in Bioengineering and Biotechnology, 2021)
Lignin exhibited numerous advantages such as plentiful functional groups, good biocompatibility, low toxicity, and high carbon content, which can be transformed into composites and carbon materials. Lignin-based materials are usually environmentally friendly and low cost, and are widely used in energy storage, environment, electronic devices, and other fields. In this review article, the pretreatment separation methods like hydrothermal process are illustrated briefly, and the properties and categories of technical lignin are introduced. Then, the latest progress of lignin-based composites and lignin-derived carbon materials is summarized. Finally, the current challenges and future developments were suggested based on our knowledge. It is expected that this review paper favored the applications of composites and lignin-derived carbon materials in the future.